The Relationship Between Position Analysis, Career Development, Leadership and Employee Performance at BAPPEDA Aceh Tamiang - Riduan, Ahmad; Azhary, Rizky; Marpaung, Al- Amin Hidayat; Hutapea, Hildasari; Hutagaol, Samsul Bahri; Supriadi (Jurnal EMT KITA, 2025)
This study aims to analyze the relationship between position analysis, career development, leadership, and employee performance at the Regional Development Planning Agency (BAPPEDA) of Aceh Tamiang Regency. This study uses a quantitative approach with a survey method. Data was obtained through a questionnaire distributed to BAPPEDA Aceh Tamiang employees, with a sample of 100 respondents selected by purposive sampling. The variables studied include job title analysis, career development, leadership, and employee performance. The data analysis technique uses multiple linear regression to test the relationship between variables. The results of the study show that position analysis has a significant influence on employee performance, where the clarity of duties and responsibilities produced through position analysis is able to increase work efficiency and effectiveness. Career development also contributes positively to employee performance, especially through training and promotion programs that provide motivation and additional competencies to employees. In addition, effective leadership has proven to be an important factor in improving employee performance through providing direction, motivation, and example. Simultaneously, job title analysis, career development, and leadership make significant contributions to employee performance, suggesting that a combination of these three variables is necessary to achieve optimal performance. This research provides practical implications for the management of BAPPEDA Aceh Tamiang to continue to improve the position analysis system, design relevant career development programs, and build inspirational leadership to improve employee performance. This research also opens up opportunities for further studies that can deepen the understanding of other factors that affect employee performance in government organizations.